Case report: Metastatic choriocarcinoma in the second trimester of a viable pregnancy with successful delivery and outcome after chemotherapy - Tian, Yalin; Yu, Jiayi; Dan, Xin; Chen, Tanglin; He, Yalin (Frontiers in Oncology, 2024)
Metastatic choriocarcinoma during viable pregnancy is rare worldwide, and neonate survival following pregnancy termination in the second trimester is uncommon. Here we report the successful delivery of a pregnancy by a patient with metastatic choriocarcinoma, who received three courses of etoposide, methotrexate, actinomycin D, cyclophosphamide, vincristine (EMA-CO) chemotherapy in the second trimester. After multidisciplinary discussions, she was administered paclitaxel and carboplatin (TC) chemotherapy. Regular contractions occurred during her first paclitaxel infusion, and a healthy infant was delivered by cesarean section at 26 +4 gestational weeks. Choriocarcinoma was not detected in the placenta. Following delivery of the pregnancy, the patient underwent total treatment comprising one cycle of TC, seven cycles of EMA-CO, and five courses of etoposide, cisplatin, methotrexate, dactinomycin (EP-EMA) chemotherapy; her serum level of beta-human chorionic gonadotropin gradually fell after chemotherapy. Uterine and pulmonary metastases shrank, and no distant metastasis or recurrence were found until the eighth course of maintenance treatment with immunotherapy. The patient received periodic chemotherapy for recurrence at the time of publishing this case report. The child was disease-free 15 + months after delivery. Despite serious metastases and complications, metastatic choriocarcinoma diagnosed in the second trimester of pregnancy can be successfully treated with minimal delay by multidisciplinary medical and nursing management.